2012
DOI: 10.1128/jvi.06504-11
|View full text |Cite
|
Sign up to set email alerts
|

Tracking Viral Evolution during a Disease Outbreak: the Rapid and Complete Selective Sweep of a Circovirus in the Endangered Echo Parakeet

Abstract: f Circoviruses are among the smallest and simplest of all viruses, but they are relatively poorly characterized. Here, we intensively sampled two sympatric parrot populations from Mauritius over a period of 11 years and screened for the circovirus Beak and feather disease virus (BFDV). During the sampling period, a severe outbreak of psittacine beak and feather disease, which is caused by BFDV, occurred in Echo parakeets. Consequently, this data set presents an ideal system for studying the evolution of a path… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
70
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(73 citation statements)
references
References 61 publications
2
70
0
Order By: Relevance
“…The oral or cloacal transmission and environmental persistence of BFDV, as well as the predisposition of young birds to become infected, suggests a potentially significant role of shared nest hollows in facilitating spillover, allowing abundant parrot species to act as reservoirs for circovirus infection in very sparse or small populations of species such as the Orangebellied Parrot. An analogous situation has been documented in Mauritius, where BFDV transmission occurs between invasive and abundant Rose-ringed Parakeets (Psittacula krameri) and the endemic, endangered Echo Parakeet (Psittacula echo) (Kundu et al, 2012).…”
Section: Discussionmentioning
confidence: 56%
See 2 more Smart Citations
“…The oral or cloacal transmission and environmental persistence of BFDV, as well as the predisposition of young birds to become infected, suggests a potentially significant role of shared nest hollows in facilitating spillover, allowing abundant parrot species to act as reservoirs for circovirus infection in very sparse or small populations of species such as the Orangebellied Parrot. An analogous situation has been documented in Mauritius, where BFDV transmission occurs between invasive and abundant Rose-ringed Parakeets (Psittacula krameri) and the endemic, endangered Echo Parakeet (Psittacula echo) (Kundu et al, 2012).…”
Section: Discussionmentioning
confidence: 56%
“…The species has been observed reusing nest hollows (Stojanovic et al, 2012) when flowering conditions are favorable. It is not surprising that PBFD infects birds through shared nest hollows, for although a degree of host specificity is seen in psittacine circoviruses, considerable host generalism is also observed in several lineages (Varsani et al, 2011;Kundu et al, 2012;Massaro et al, 2012). Furthermore, the likely prolonged environmental persistence of circovirus virions (Raidal and Cross, 1994;Yilmaz and Kaleta, 2004) provides a mechanism by which transmission can occur in otherwise ecologically disconnected species.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…BFDV occurs in many wild and captive parrot populations worldwide, with the potential to cause high mortality (25,26). Accordingly, it is considered a significant conservation threat and has been implicated in parrot declines in Australia and globally (27)(28)(29)(30). BFDV possesses a single-stranded DNA genome of ∼2,000 nucleotides (31).…”
Section: Significancementioning
confidence: 99%
“…Olvera et al (2007) believe the capsid gene is a more suitable marker for phylogenetic and epidemiological analyses and the characteristic of low recombination rates increases the detection accuracy of the signatures of positive selection on circovirus. Several studies have shown that natural selection plays an important role in the diversification of capsid proteins since they can evade the host immune system through amino acid replacement (Kundu et al, 2012;Olvera et al, 2007). Sequence differences between capsid protein genes could alter the antigenicity and cause cross-species transmission by changes in receptor specificity (Baranowski et al, 2001).…”
Section: Introductionmentioning
confidence: 99%